2007
DOI: 10.1007/s10897-007-9094-3
|View full text |Cite
|
Sign up to set email alerts
|

What do Patients Prefer: Informed Consent Models for Genetic Carrier Testing

Abstract: The recent increased number of conditions for which patients can undergo genetic carrier testing raises the question of how best to obtain pre-test informed consent. Clinical approaches vary from a minimalist model to a model where patients are given detailed information about all conditions to be screened for. Few data exist as to patient preferences, or how information impacts decision-making. Eight high-literacy focus groups were conducted to assess the knowledge and preferences of pregnant patients and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 12 publications
3
38
0
Order By: Relevance
“…These authors have also reported that many would prefer to be tested for haemoglobinopathy carrier status before conception (Locock and Kai 2008). In the USA (Ormond et al 2007) and Australia (Cousens et al 2010), prenatal carrier screening for haemoglobinopathies occurs ad hoc, yet there are similar findings regarding the lack of awareness of screening. In practice, screening of the population for haemoglobinopathy carrier status may occur incidentally in primary care as a result of blood being taken for other reasons.…”
Section: Carrier Screening For Haemoglobinopathiesmentioning
confidence: 92%
“…These authors have also reported that many would prefer to be tested for haemoglobinopathy carrier status before conception (Locock and Kai 2008). In the USA (Ormond et al 2007) and Australia (Cousens et al 2010), prenatal carrier screening for haemoglobinopathies occurs ad hoc, yet there are similar findings regarding the lack of awareness of screening. In practice, screening of the population for haemoglobinopathy carrier status may occur incidentally in primary care as a result of blood being taken for other reasons.…”
Section: Carrier Screening For Haemoglobinopathiesmentioning
confidence: 92%
“…In the United States of America, pregnant women were also found to have a lack of awareness of genetic testing, and if they had undergone carrier testing, they often could not recall undergoing the test. 39 Ormond and colleagues found that many pregnant women feel overwhelmed about the numerous tests offered to them, and they do not have a clear understanding about what any of the tests are designed to detect. 39 It should be noted that antenatal screening for thalassaemia often occurs in the context of the first antenatal visit, at which time a considerable amount of information about testing and care during pregnancy is provided 40 and recall may be poor if the information is not judged to be of particular relevance.…”
Section: Mandatory Screeningmentioning
confidence: 99%
“…39 Ormond and colleagues found that many pregnant women feel overwhelmed about the numerous tests offered to them, and they do not have a clear understanding about what any of the tests are designed to detect. 39 It should be noted that antenatal screening for thalassaemia often occurs in the context of the first antenatal visit, at which time a considerable amount of information about testing and care during pregnancy is provided 40 and recall may be poor if the information is not judged to be of particular relevance. 41 Informed consent for thalassaemia carrier screening A number of different guidelines have recommended that informed consent should be a requirement for all genetic screening programmes.…”
Section: Mandatory Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[14][15][16] These realities dictate that parents play a meaningful role in deciding whether or not their child should participate in such a study. [17][18][19][20] The study was designed to determine parents' interest in screening, their reasons for accepting or declining, family adaptation to learning about carrier status, and the early developmental progress of identified infants. Parents were recruited in the hospital shortly after their child's birth; those interested in hearing about the study were given a brochure and consent form by a bilingual research assistant (RA).…”
Section: The Newborn Screening Contextmentioning
confidence: 99%